U.S. Foreign Policy Towards Iranian Nuclear Threat from Bill Clinton to Donald Trump Administration - Anak Agung Banyu Perwita; Muhammad Ilham Razak (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2020)
Iranian nuclear threat remains one of the most pressing issue throughout the history of US foreign policy. Ever since the islamic revolution occured in Iran in 1979, Iran hostile activities in Middle East has been a major threat for US security interest, in particular when Iran started to build its ambition to build its nuclear weapon. Having said that, this article aims to discuss US foreign policy toward the threat of Iranian nuclear program from Bill Clinton administration until Trump Administration. By using thematic analysis from Braun and Clarke, this article would scrutinize the internal and external factors of US foreign policy toward Iran and then seeks to understand the change and continuity of US foreign policy from Bill Clinton until Trump administration. From the analysis, it was found that US foreign policy has been influenced a lot by its internal and external factors, resulting in different responses of US foreign policy in each administration. Moreover, US foreign policy has been consistent to put Iranian nuclear threat as its major security threat despite differ in its foreign policy. However, the withdrawal of US under Trump in Joint Comprehensive Plan Of Action (JCPOA) deal has provided an inconsistency of US foreign policy with its previous administration.